Calibrated ages of Great Heath peat core from the USA - Michael Clifford; Jonathan Nichols; Yongsong Huang (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.